A family of salamo-type trinuclear Co(II) and Ni(II) complexes: Structural characterization, Hirshfeld surface analysis and fluorescent properties. (1st August 2021) - Li, Peng; Li, Shi-Zhen; Wei, Yu-Xin; Dong, Wen Kui
Graphical abstract: Three trinuclear complexes 1 -3 possessed inversion centers have been successfully synthesized by wet-chemical method using asymmetric salamo-based polydentate chelating ligand (H2 L) with Co(OAc)2 ·4H2 O and Ni(OAc)2 ·4H2 O, respectively. Abstract: Three trinuclear complexes, [CoL(MeOH)( μ -OAc)2 Co] (1 ), [CoL(EtOH)( μ -OAc)2 Co]·2CH3 CH2 OH (2 ) and [NiL(MeOH)( μ -OAc)2 Ni]·2CH3 OH (3 ) have been successfully synthesized by wet-chemical method using asymmetric salamo-based polydentate chelating ligand (H2 L) with transition metal(II) acetate (Co(OAc)2 ·4H2 O or Ni(OAc)2 ·4H2 O). The ligand H2 L with N2 O2 coordination cavity can accommodate transition metals, at the same time, the oxygen atoms of the phenolic hydroxyl groups can bridge the metal atoms to obtain muiltnuclear metal complexes. There are inversion centers in complexes 1 –3 and all M(II) atoms possess six-coordinated distorted octahedral geometries. Complexes 1 and 3 are further assembled into extended two-dimensional supramolecular via intermolecular interactions, but complex 2 forms three-dimensional supramolecular structure. The interactions were quantitatively determined by Hirshfeld surfaces analyses. Significantly, complexes 1 –3 have been characterized by elemental analyses, IR spectra, UV–Vis spectroscopy and X-ray crystallography analyses. Fluorescence properties were also investigated.